Effects of dexmedetomidine-ropivacaine assisted combined spinal-epidural anesthesia on neutrophil-lymphocyte ratio and postoperative delirium in elderly patients with intertrochanteric femoral fracture - Bai, Lili; Zhao, Lina; Jia, Fang; Liu, Ying; Li, Ping (Frontiers in Pharmacology, 2025)
ObjectiveIntertrochanteric femoral fracture (IFF) is a public issue in the old. Combined spinal-epidural anesthesia (CSEA) is commonly utilized for lower limb orthopedic surgery in elderly patients. Therefore, this study explored the application of dexmedetomidine (Dex) and ropivacaine (Rop) assisted CSEA in elderly IFF patients.MethodsTotally 187 elderly IFF patients were assigned into the Rop assisted CSEA (Rop-CSEA), low-dose Dex-Rop assisted CSEA (low Dex and Rop-CSEA) and high-dose Dex-Rop assisted CSEA (high Dex and Rop-CSEA) groups. We compared block effects, hemodynamic indicators [heart rate (HR)/respiratory rate (RR)/mean arterial pressure (MAP)] at time before anesthesia (T0)/skin incision (T1)/10 min postoperatively (T2)/suture postoperatively (T3)/anesthesia recovery (T4), postoperative pain mediator release [substance P (SP)/prostaglandin E2 (PGE2)/5-hydroxytryptamine (5-HT)], neutrophil-lymphocyte ratio (NLR), adverse reactions, delirium and cognitive dysfunction incidence.ResultsCompared with the Rop-CSEA group, low/high Dex and Rop-CSEA groups had shortened onset times, prolonged recovery times in sensory/motor block, elevated HR/RR/MAP, repressed pain mediator release, and reduced postoperative delirium and cognitive dysfunction incidences. HR/RR/MAP exhibited reductions followed by elevations at T2-T4, and SP/PGE2/5-HT levels revealed elevations in all groups postoperatively. NLR level displayed enhancement followed by reduction, and NLR in the low/high Dex and Rop-CSEA groups was abated on postoperative days 1–5. Total incidence of adverse reactions in the high Dex and Rop-CSEA group was enhanced.ConclusionDex and Rop assisted CSEA shortens the onset time of anesthesia, maintains perioperative hemodynamic stability, inhibits pain mediator release, reduces postoperative NLR level and the incidence of delirium and cognitive dysfunction in IFF patients.